Systematic taxonomy of middle Miocene Sphaeroidinellopsis (planktonic foraminifera). (3rd July 2021) - Fabbrini, Alessio; Zaminga, Ilaria; Ezard, Thomas H. G.; Wade, Bridget S.
Abstract : The taxonomy and phylogeny of the Miocene to Recent genus Sphaeroidinellopsis have been documented in previous studies, but the evolution of this lineage remains unclear. Some authors have debated this genus in the past, choosing a variety of parameters to discriminate the morphospecies. Here we present new scanning electron microscope analyses of specimens from Ocean Drilling Program (ODP) Site 925 (Ceara Rise, western equatorial Atlantic) and ODP Site 959 (Deep Ivorian Basin, eastern equatorial Atlantic). Our study reveals transitional individuals Sphaeroidinellopsis disjuncta – Sphaeroidinellopsis kochi, a speciation event never described previously. These transitional specimens are characterized by extreme morphological features such as elongated and sac-like final chambers, requiring amendments to the current classification and taxonomy of these morphospecies. In this paper, an alternative hypothesis is presented and discussed, to assess these new observations within the evolutionary mosaic of Sphaeroidinellopsis .